2019
DOI: 10.1101/791913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An unbiased high-throughput drug screen reveals a potential therapeutic vulnerability in the most lethal molecular subtype of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is predicted to become the second leading cause of cancer-related deaths in the United States by 2020, due in part to innate resistance to widely used chemotherapeutic agents and limited knowledge about key molecular factors that drive tumor aggression. We previously reported a novel negative prognostic biomarker, keratin 17 (K17), whose overexpression in cancer results in shortened patient survival. In this study, we aimed to determine the predictive value of K17 and ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Prior work has shown that pancreatic cancers expressing high levels of K17 are resistant to commonly deployed first-line chemotherapeutic agents, notably gemcitabine (Wang et al 2011; Aung et al 2018; Pan et al 2020; Yao et al 2020). The finding that K17-phosphorylation at the N-terminus S10-13 is regulated by a PKC/MEK/RSK pathway is important because it suggests that K17 may be sensitive to targeted kinase inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has shown that pancreatic cancers expressing high levels of K17 are resistant to commonly deployed first-line chemotherapeutic agents, notably gemcitabine (Wang et al 2011; Aung et al 2018; Pan et al 2020; Yao et al 2020). The finding that K17-phosphorylation at the N-terminus S10-13 is regulated by a PKC/MEK/RSK pathway is important because it suggests that K17 may be sensitive to targeted kinase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In carcinomas of the lung, pancreas, cervix, and other sites, K17 is reexpressed for reasons that are not fully understood (Real et al 1993;Mikami et al 2015;Roa-Pena et al 2019;Roa-Pena et al 2021). In PDAC, K17 expression is a hallmark of the basallike subtype, which is associated with the shortest patient survival and resistance to first-line therapies (Wang et al 2011;Grasso et al 2017;Aung et al 2018;Roa-Pena et al 2019;Pan et al 2020;Roa-Pena et al 2021). Growing evidence, however, suggests that K17 expression contributes to a variety of cancer hallmarks, suggesting its role as a potent oncoprotein (Ide et al 2012;Mikami et al 2015;Wu et al 2017;Liu et al 2018;Wang et al 2019;Liu et al 2020; Baraks et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…All experimental procedures were approved by the Institutional Animal Care and Use Committee (IACUC) at Stony Brook University and Yale University and are in accordance with the Guide for the Care and Use of Laboratory Animals from the National Institutes of Health. As previously described 9 , KPC cells with or without K17 expression were harvested during log-phase growth and resuspended in DMEM (Gibco) with Matrigel (Life Sciences) at a ratio of 1:1, to a final of 1,000 cells in a 30 μl volume. Cells were orthotopically implanted into the head of the pancreas of c57B6J mice.…”
Section: Murine Orthotopic Xenograft Studiesmentioning
confidence: 99%
“…These findings highlight novel lines of investigation of surrogate biomarkers in molecular subtypes that may aid the development of more effective targeted therapy. We independently reported that keratin 17 (K17), one of the signature genes overexpressed in the Moffitt basal-like subtype 4 , is a novel negative prognostic and predictive biomarker in PDAC [7][8][9] . We also showed that K17 expression drives resistance to Gemcitabine (Gem) and 5-fluorouracil (5-FU) 9 , two key components of the main chemotherapeutic regimens for pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation